MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN (POE) PADA MATERI LARUTAN ELEKTROLIT-NONELEKTROLIT DAN REAKSI REDUKSI OKSIDASI - Siti Rahmah; Muhammad Kusasi (Universitas Lambung Mangkurat, 2016)
Abstract. This study aims to determine the increase in critical thinking skills, learning outcomes and student activity using strategies Predict-Observe-Explain (POE) on the material electrolyte-non electrolyte solution and oxidation reduction reaction. This research was a classroom action research (CAR) conducted in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. The subjects were 36 students. The data collection includes pieces of observation and tests. The results showed an increase in critical thinking skills, 73.84% with a critical category from first cycle to 93.29% categorized as very critical in the second cycle. Cognitive learning outcomes increase, 79.94 with a good category in the first cycle to 90.50 with the very well category in the second cycle. Affective learning outcomes increased from 10.29 in both categories in the first cycle to 12.12 with both categories at the second cycle. Psychomotor learning outcomes increased from 60.42 at the first cycle to 83.28 at the second cycle. Activities of students increased from 27.17 with quite active category in the first cycle to 33.5 with the active category in the second cycle. Based on these results it can be concluded that the use of the POE strategy can improve critical thinking skills and student learning outcomes in the material electrolyte-non electrolyte solution and oxidation reduction reaction.Keywords: POE strategy, critical thinking skills, learning outcomes